Penguatan Profil Pelajar Pancasila (P5) bagi Siswa SMA Alam Al Ghifari Blitar - Muchson, Mochamad; Kusumaningtyas, Dian; Damayanti, Susi; Alvian, Mohammad; Ni’mah, Elsha Ulfatun (Universitas Nurul Jadid, 2025)
The Merdeka Curriculum emphasizes flexible learning through three main components: intracurricular learning, co-curricular activities through the Strengthening Pancasila Student Profile Project (P5), and extracurricular activities. P5 is designed as an interdisciplinary learning approach focused on solving real-world problems while serving as a means to achieve the six dimensions of the Pancasila Student Profile. This community service project was carried out through socialization, workshops, and mentoring sessions with students in implementing P5 under the theme